Long-term scarring from institutional labelling: The risk of NEET of students from schools for learning disability in Germany - Laura Menze; Heike Solga; Reinhard Pollak (Acta Sociologica, 2022)
This article demonstrates the disadvantages that students leaving special needs schools (Förderschule) face in their school-to-work transition in Germany. We analyse whether the institutional label of `having attended a special needs school' – beyond and above low school attainment – results in scarring effects for students' chances of integration into training and employment after leaving school. We focus on students classified as having learning disability (Lernbehinderung), the largest group among students with special educational needs (SEN) and examine their NEET risk compared to equally low-attaining students from general schools at age 20/21. The analyses are based on rare longitudinal data for SEN students, the German National Educational Panel Study. Employing matching and regression techniques, we find that the label of `having attended a special needs school' does generate long-term scars above and beyond low school attainment. However, this is only the case for school leavers with a lower secondary school certificate but not for those without school certificate.
doi:10.25384/SAGE.20406043.v1
Keywords: 320; educational attainment; learning disability; NEET; school-to-work transitions; special educational needs; vocational education and training; Germany